The Influence of Price, Driving Safety, and Service Quality on GoRide Customer Satisfaction Using the SEM-PLS Method in Tegal Regency - Kenedy, John; Hidayat, Ade Nurul; Widya, Adi Rusdi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the effect of price, riding safety, and service quality on GoRide customer satisfaction in Tegal Regency using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected from 100 GoRide users through a 5-point Likert-scale questionnaire. SmartPLS 4.1.0.9 was used to assess the validity and reliability of the research instrument, and to evaluate both the measurement (outer) and structural (inner) models. The results show that all outer loading values exceed 0.7 and Average Variance Extracted (AVE) values are above 0.5, indicating good validity and reliability. The inner model analysis confirms that price, riding safety, and service quality significantly affect customer satisfaction, with riding safety having the strongest impact. These findings suggest that service providers should focus on improving safety standards, enhancing service quality, and ensuring price transparency to boost customer satisfaction.